2021
DOI: 10.1002/nau.24651
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and satisfaction with telephone consultation of follow‐up patients in neuro‐urology: Experience of the COVID‐19 pandemic

Abstract: The COVID-19 pandemic led to limit patients' visits to the neuro-urology department. Telemedicine was seen as a pragmatic solution to provide follow-up care. This study aimed to assess the efficiency and satisfaction of a telephone consultation in neuro-urology. Methods: During the pandemic, the scheduled medical visits were converted into telephone consultation. For each teleconsultation, the physician assessed the efficiency and the patient-rated global satisfaction of the teleconsultation. The physician and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…The lack of visual cues interfered with the clinicians' ability to interact with their patients, as they could not access non-verbal communication. This was especially problematic for physicians with patients with hearing or cognitive impairments and those with language barriers [25,42,49]. From the clinicians' perspective, teleconsultation using video platforms had added value by giving them access to non-verbal communication allowing them to visually and verbally assess their patients' responses and reactions.…”
Section: Key Service Process Factors In Patients' Teleconsultation Ex...mentioning
confidence: 99%
“…The lack of visual cues interfered with the clinicians' ability to interact with their patients, as they could not access non-verbal communication. This was especially problematic for physicians with patients with hearing or cognitive impairments and those with language barriers [25,42,49]. From the clinicians' perspective, teleconsultation using video platforms had added value by giving them access to non-verbal communication allowing them to visually and verbally assess their patients' responses and reactions.…”
Section: Key Service Process Factors In Patients' Teleconsultation Ex...mentioning
confidence: 99%
“…Ramaswamy et al [ 24 ] analyzed Press Ganey patient satisfaction surveys from over 38,000 patients including 620 video visits and found that satisfaction scores were significantly higher for video visits compared to in-person visits (94.9% vs 92.5%, P < 0.001). Studies across multiple subspecialty disciplines within urology including urologic oncology, pediatric urology, neuro-urology, and female pelvic and reconstructive medicine have demonstrated high satisfaction rates with telemedicine during the pandemic [ 25 29 ]. Most recently, Shiff et al examined patient satisfaction rates in a single andrology clinic and found that the majority of patients were satisfied with a telephone-mediated visit as a substitute for an in-person visit during the COVID-19 pandemic.…”
Section: The Benefitsmentioning
confidence: 99%
“…Four studies that used telephone and video modalities indicated that most patients felt communication was effective and su cient with teleconsultations [44,45,53,57]. Contrarily, clinicians expressed more negative experiences towards communication in ve of the studies that used both telephone and video modalities, especially regarding concerns about decreased personal connections and risk of misunderstanding [26,42,49,54,55]. Meeting logistical needs (convenience): A contributing factor A systematic review of telehealth services pre-COVID-19 concluded that convenience (travel-saving, time-saving, and cost-saving) is one of the most signi cant factors in uencing patients' satisfaction [71].…”
Section: Clinical Activities: Clinicians' Moral Distress and The Role Of Physical Examinationmentioning
confidence: 99%